Relationship between dialysis adequacy and cognitive function in hemodialysis patients - Şahin, Ahmet Ziya; Usalan, Özlem; Demir, Bahadır; Şahin, Şengül Kocamer; Erdur, Mehmet Fatih; Usalan, Celalettin (Ukrainian Journal of Nephrology and Dialysis, 2023)
The prevalence of cognitive impairment is extremely high in dialysis patients, and it has been hypothesized that low urea clearance has an impact on cognitive impairment. However, several other studies conducted in the era of high-flux dialysis have not shown an association between lower Kt/V and poorer cognitive function. Therefore, studies that directly examine the relationship between dialysis adequacy and cognitive function in hemodialysis patients are essential. The present study aimed to investigate the cognitive functions of hemodialysis patients and their relationship with dialysis adequacy. Methods. This cross-sectional observational study included 100 patients and 100 healthy volunteers. Dialysis adequacy was assessed by the Kt/V ratio in the previous month. The Mini-Mental State Examination (MMSE), the Montreal Cognitive Assessment Test (MoCA), and the Clock Drawing Test (CDT) were used to assess cognitive function. Multiple regression analysis was used to determine the significant association between the cognitive assessments and the independent variables (Kt/V, age, education, hemoglobin, and albumin). Results. There were no significant differences between patients and controls in age and sex. Patients had a mean Kt/V ratio of 1.52±0.29. MMSE, MoCA, and CDT were lower in patients than in controls. There were strong positive correlations between MMSE and Kt/V (r = 0.81), MoCA and Kt/V (r = 0.84), CDT and Kt/V (r = 0.79). Conclusion. Cognitive functions in hemodialysis patients were significantly decreased compared with healthy controls and associated with dialysis adequacy. Dialysis adequacy should be questioned in patients with low cognitive function.